2023
DOI: 10.3390/brainsci13071065
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideations in Major Depressed Subjects: Role of the Temporal Dynamics of Anhedonia

Abstract: Given the limited data available in the literature, the aim of this study was to investigate the potential role played by the temporal dynamics of anhedonia (lifelong anhedonia and recent changes in anhedonia) in the occurrence of suicidal ideations in major depressed subjects. The clinical data of 285 major depressed subjects recruited from the database of the Erasme Hospital Sleep Laboratory were analyzed. A score on item nine of the Beck Depression Inventory (BDI-II) ≥1 and/or an identification during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…Consistent with the data currently available in the literature, we confirmed that ID (67.0%) and OSAS (42.0%) are frequent comorbidities for MDD patients [44,45]. Furthermore, in this study, we demonstrated that 58.4% of MDD patients with OSAS presented a comorbid ID, which seems to indicate a more frequent occurrence of insomnia complaints in cases of OSAS for MDD patients than for the other subpopulations currently studied for COMISA [12,13,18].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the data currently available in the literature, we confirmed that ID (67.0%) and OSAS (42.0%) are frequent comorbidities for MDD patients [44,45]. Furthermore, in this study, we demonstrated that 58.4% of MDD patients with OSAS presented a comorbid ID, which seems to indicate a more frequent occurrence of insomnia complaints in cases of OSAS for MDD patients than for the other subpopulations currently studied for COMISA [12,13,18].…”
Section: Discussionsupporting
confidence: 91%